Hypoxia and the Kynurenine Pathway: Implications and Therapeutic Prospects in Alzheimer's Disease. (10th November 2021) - Adeyemi, Oluyomi Stephen; Awakan, Oluwakemi Josephine; Afolabi, Lawrence Boluwatife; Rotimi, Damilare Emmanuel; Oluwayemi, Elizabeth; Otuechere, Chiagoziem A.; Ibraheem, Omodele; Elebiyo, Tobiloba Chritiana; Alejolowo, Omokolade; Arowolo, Afolake T.
Abstract : Neurodegenerative diseases (NDs) like Alzheimer's disease, multiple sclerosis, amyotrophic lateral sclerosis, Parkinson's disease, and Huntington's disease predominantly pose a significant socioeconomic burden. Characterized by progressive neural dysfunction coupled with motor or intellectual impairment, the pathogenesis of ND may result from contributions of certain environmental and molecular factors. One such condition is hypoxia, characterized by reduced organ/tissue exposure to oxygen. Reduced oxygen supply often occurs during the pathogenesis of ND and the aging process. Despite the well-established relationship between these two conditions (i.e., hypoxia and ND), the underlying molecular events or mechanisms connecting hypoxia to ND remain ill-defined. However, the relatedness may stem from the protective or deleterious effects of the transcription factor, hypoxia-inducible factor 1-alpha (HIF-1 α ). The upregulation of HIF-1 α occurs in the pathogenesis of most NDs. The dual function of HIF-1 α in acting as a "killer factor" or a "protective factor" depends on the prevailing local cellular condition. The kynurenine pathway is a metabolic pathway involved in the oxidative breakdown of tryptophan. It is essential in neurotransmission and immune function and, like hypoxia, associated with ND. Thus, a good understanding of factors, including hypoxia (i.e., the biochemical implication of HIF-1 α ) and kynurenine pathway activation in NDs, focusing on Alzheimer's disease could prove beneficial to new therapeutic approaches for this disease, thus the aim of this review.